A Novel Neutrosophic Relational Maps Approach for Business Process Maturity Assessment in Logistics and Trade - Xuyou Sun; Kun Xue (Neutrosophic Sets and Systems)
In today’s rapidly evolving logistics and trade environments, assessing the maturity of business processes is crucial for sustaining competitive advantage. However, traditional maturity models often fail to accommodate the inherent uncertainties and indeterminacies in real-world logistics operations. To address this gap, we propose a novel mathematical framework based on Neutrosophic Relational Maps (NRMs) for Business Process Maturity Assessment (BPMA). Unlike existing methods, our approach introduces innovative neutrosophic weighting functions and a new dynamic updating mechanism to handle the simultaneous presence of truth, falsehood, and indeterminacy in logistical relationships. We formulate the mathematical foundations of this approach through new matrix operations and neutrosophic thresholding equations, supported by a fully calculated step-by-step example illustrating the BPMA in a hypothetical logistics scenario. Finally, we provide an in-depth analysis and discussion of the implications, advantages, and limitations of the proposed model, articulated in clear and concise English to ensure accessibility and reproducibility.